Prevalence and Associated Factors of Complains on Depression, Anxiety, and Stress in University Students: An Extensive Population-Based Survey in China - Yu, Yanling; Yan, Wangwang; Yu, Jiadan; Xu, Yangfan; Wang, Dan; Wang, Yuling (Frontiers in Psychology, 2022)
Mental health issues are becoming increasingly prevalent amongst university students. However, research on the psychological profile of the general university population is relatively limited. Thus, this study analyses the current state of university students’ psychological conditions; the demographic differences in depression, anxiety and stress and the influencing factors. The objectives are to provide additional appropriate guidance in mental health for university students with different demographic characteristics. A cross-sectional study of 6032 university students nationwide was conducted from October 2020 to January 2021. A randomised Jung group sampling method was used to select the study participants, and the 21-item Depression, Anxiety and Stress Scale (DASS) was used. P<0.05 in the final model were considered statistically significant. The number of university students with no symptoms of depression, anxiety or stress was 3,751 (62.2%). The odds of developing depression were higher amongst anxious respondents (AOR = 23.417, 95% CI: 19.706, 27.826) and senior year (AOR = 2.210, 95% CI: 1.657, 2.947) than their counterparts. Students with ‘myopia’ were 1.263 times more likely to be anxious (AOR = 1.263, 95% CI: 1.042–1.530). In terms of ‘impaired’ or not, impaired is defined as any injury, such as sprain, strain and fracture, ‘impaired’ university students were 1.321 times more likely to be anxious (AOR = 1.321, 95% CI: 1.064–1.641). Furthermore, history of impairment and myopia increased the odds of stress by 1.305 (AOR = 1.305, 95% CI: 1.022–1.667) and 1.305 (AOR = 1.305, 95% CI: 1.012–1.683), respectively. Myopia, physical-activity-related injury (PARI) and irrational eating habits are risk factors for anxiety and stress. Males, upper grades, low parental education and irrational eating habits are risk factors for depression. Low physical activity levels are also an influential factor for depression. DASS consists of interchangeable risk factors and multiple symptoms of DASS may coexist.